Handwriting recognition - Ocampo, John Arvee L. (2002)
We present an Offline Handwriting Recognition Program. The software has two major components. Pre-processing of a given image, and Recognition which makes use of an Artificial Neural Network. We show the capability of the Neural Network in recognizing handwritten text as well as computer printed text.